Penerapan model problem based learning berbantuan media diorama untuk meningkatkan hasil belajar peserta didik pada pembelajaran IPAS kelas IV sekolah dasar - Dyah Rahma Julia Mardani; Retno Winarni; Supianto Supianto (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2024)
The purpose of this study is to improve the learning outcomes of science through the application of problem based learning model assisted by diorama media on fourth grade students of SD Negeri Semanggi Lor Surakarta. This research is a descriptive research with Action Research Approach Class (PTK) procedures Kemmis and Mc Taggart conducted in two cycles, each cycle consists of two meetings and four stages: planning, action, observation, and reflection. The subjects of this study were class teachers and fourth grade students at SDN Semanggi Lor Surakarta for the 2023/2024 academic year, which numbered 28. Data collection techniques in this study are tests, observations, interviews, and documentation. The technique of testing the validity of the data in this study using the validity of the content, source triangulation and triangulation techniques. Data analysis techniques in this study using Miles-Huberman interactive analysis model consisting of data collection, data reduction, data presentation, and conclusion or verification. Learning outcomes are said to be successful if they meet the indicators of research achievement (90% or 26 out of 28 students achieve KKTP ≥75). This study obtained the results of classical completeness in the pretest cycle I Meeting 1 by 32.14% increased in the post test to 75%, while the pretest at meeting 2 by 3.57% increased to 85.71% in the post test. Classical completeness in the second cycle of meeting 1 obtained 25% in the pretest increased in the post to 89.29% then at meeting 2 obtained 82.14% in the pretest and increased to 96.43% in the post. Based on these results, it can be concluded that the application of the diorama media-assisted problem based learning model can improve the learning outcomes of students in the “water cycle” material for learning IPAS class IVA SDN Semanggi Lor Surakarta for the 2023/2024 academic year.